2018
DOI: 10.1111/btp.12537
|View full text |Cite
|
Sign up to set email alerts
|

Dietary niche separation of rodents and shrews in an African savanna

Abstract: While niche separation and relationships with environmental conditions of large mammals of the African savanna have been studied intensively, less conspicuous components have not received similar attention. This is the case of Kafue National Park (KNP), Zambia, where mechanisms supporting coexistence among rodent and shrew species remain unclear, much less the influence of fire on their dietary resource use. Here, we use stable carbon and nitrogen isotopes to assess dietary resource use and partitioning among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It appears to be caused by niche partitioning among sympatric species. Intra‐ or interspecific competition occurs for the acquisition of limited and overlapped resources between the same or different species (Namukonde et al 2018). To avoid competition, rodents utilize different resources by niche partitioning (Finke and Snyder 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It appears to be caused by niche partitioning among sympatric species. Intra‐ or interspecific competition occurs for the acquisition of limited and overlapped resources between the same or different species (Namukonde et al 2018). To avoid competition, rodents utilize different resources by niche partitioning (Finke and Snyder 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Maishanu et al (2017) reported that burnt areas have higher biomass yield than unburnt areas and might promote higher recruitment. The observed results might be a function of increased predation in the burnt sites regardless of improved food quality (Block et al, 2016; Morris et al, 2011; Namukonde et al, 2018), thus affecting the recruitment rates. Seasonality favoured higher recruitment in burnt compared to unburnt areas.…”
Section: Discussionmentioning
confidence: 99%
“…natalensis recruitment were higher in unburnt than in the burnt areas although the differences were not statistically significant. Namukonde et al (2018) reported that competition for resources might be more relaxed in burnt areas since fire acts as a temporary and spatial disturbance in the context of the stochastic community process. In addition, Maishanu et al (2017) reported that burnt areas have higher biomass yield than unburnt areas and might promote higher recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Species habitat and diet overlaps have been previously recorded, and may reflect resource availability (Forero et al 2004, Soininen et al 2015, Reif et al 2016, Dehnhard et al 2019). Similarly, negative correlations between habitat use and activity patterns have been invoked to explain coexistence among sympatric mammals (Namukonde et al 2018). However, the positive correlation between habitat and host functional redundancy was unique to the metric of FR, raising doubts about its generality.…”
Section: Discussionmentioning
confidence: 99%